OP0125 Replication of GWAS of Response to TNF Inhibitors in Patients with Rheumatoid Arthritis. (9th June 2015) - Ferreiro-Iglesias, A.; Montes, A.; Pérez-Pampín, E.; Carreira, P.; Joven, B.; Caliz, R.; Ferrer, M.A.; Moreno-Ramos, M.J.; Raya, E.; Magro, C.; Vasilopoulos, Y.; Sarafidou, T.; et al.
Abstract : Background: Three large GWAs (1-3) examining the response to TNF inhibitors have provided evidence suggesting 16 SNP associations, but none of them reached the GWAS significance threshold. Objectives: We aim to replicate association of the 16 SNPs with TNFi response in an independent sample collection. Methods: A total of 755 European RA patients receiving TNFi (397 infliximab, 155 etanercept, and 203 adalimumab) were included. Response was evaluated either as change in the disease activity score using 28 joints (ΔDAS28) between baseline and 3, 6 and 12 months of treatment, or as classification according to the EULAR response criteria (good + moderate responders vs. non responders) at the same time points. The genotypes of the 16 SNPs were obtained with a single-base extension methodology. We considered the SNPs according to an additive model in linear and logistic regression analyses, for ΔDAS28 and EULAR criteria, respectively. Baseline DAS28, gender and treatment were considered as covariates. Results: All the SNPs were successfully genotyped (call rate=99.5%; HWE>0.05). None of them was associated with response to TNFi at any time of follow-up. However, NUBPL rs2378945 minor allele (A) showed the same trend as the reported by Mirkov et al. (B = -0.14, 95% CI -0.31-0.03, P=0.10 for ΔDAS28 at 3 months as reported). This trend became a significant association after stratifying by drug, in the subgroup treated with etanercept (B = -0.50, 95% CI (-0.82, -0.17), P=0.003), but no association or trend was identified with the other drugs. Conclusions: We have found a specific association with response to etanercept of NUBPL rs2378945, which is an analysis not reported in the original GWAS and, therefore, not amounting to replication. None of the other 15 associations was replicated, indicating that none of the results from these GWAS could still be taken as validated. References: Mirkov et al. Ann Rheum Dis. 2013 Aug;72(8):1375-81 Plant et al. Arthritis Rheum. 2011 Mar;63(3):645-53 Cui et al. Rheum Dis Clin North Am. 2009 Nov;35(4):745-57 Acknowledgements: Instituto de Salud Carlos III (Spain), grants PI11/01048, PI12/01909 and RD12/0009/0008 that are partially financed by the European Regional Development Fund Disclosure of Interest: None declared